Modifiable risk factors for anemia among women of childbearing age in sub-saharan Africa (2015–2023) - Beminate Lemma Seifu; Yohannes Mekuria Negussie; Angwach Abrham Asnake; Bezawit Melak Fente; Zufan Alamrie Asmare; Mamaru Melkam; Meklit Melaku Bezie; Alemayehu Kasu Gebrehana; Sintayehu Simie Tsega; Hiwot Atlaye Asebe (BMC Public Health)
Abstract Background The Sustainable Development Goals Target 2.2 aims to eliminate all forms of malnutrition, including anemia, while the World Health Assembly targets a 50% reduction in anemia among women of childbearing age by 2025. Despite these efforts, global anemia prevalence among women has only slightly decreased from 31% to 30% between 2000 and 2019. Therefore, identifying modifiable risk factors for anemia among women of childbearing age in Africa is crucial for developing evidence-based interventions and achieving these goals. Methods We conducted an analysis of the most recent Demographic and Health Surveys datasets from 21 Sub-Saharan Africa (SSA) countries, which were carried out between 2015 and 2023. Using multilevel multinomial regression models, we calculated the Adjusted Odds Ratio (AOR) with a 95% Confidence Interval, and subsequently estimated the Population Attributable Fraction (PAF) based on these AOR values. Results The study consisted of 168,417 women of childbearing age [–] (15-49) from 21 SSA. The highest proportion of moderate to severe anemia was linked to the type of contraceptive method used (PAF = 53.11%). This was followed by the lack of health insurance coverage (PAF = 37.92%). Other significant factors included poverty (PAF = 11.50%), no formal education (PAF = 18.01%), high parity (PAF = 5.78%), and the use of unimproved drinking water sources (PAF = 3.88%). These 5 modifiable risk factors were associated with 80.60% (95%CI, 77.60-83.40%) moderate/severe anemia in SSA. Conclusion In a cross-sectional study involving 21 SSA nations, we identified 5 modifiable risk factors associated with anemia among women of childbearing age in SSA. These factors should be a priority for policymakers when planning future interventions to address anemia in SSA’s women’s health.